School adoption program kick-start / Zaaba Ahmad - Ahmad, Zaaba (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
The project director, Zaaba Ahmad hoped that this men-tor-mentee programme would be a platform to establish a good partnership between the two parties. 32 students from UiTM were selected from various faculties to assist 32 Year Five students in their English subject. Concurrently, 16 lecturers were present to monitor and assist the mentors to ensure the effectiveness and smooth running of the programme.